Teen Titans. Volume 4, Light and Dark - Lobdell, Scott; Bedard, Tony (New 52., 2014)
"The Teen Titans face off against one of their quintesential rivals for the first time in The New 52: the extradimensional demon lord Trigon! The demon Trigon triumphs over the Teen Titans, turning one of their own against the team! As he begins to turn Manhattan into a staging ground for a demonic takeover of the planet, the Titans must mend the cracks formed between them if they stand any chance against the demonic villains and his corrupted children"--